TRADISI REBO KASAN SEBAGAI AKTIVITAS KEBERAGAMAAN MASYARAKAT CIGALONTANG SINGAPARNA TASIKMALAYA - Setiawan, Wawan (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
The researcher observed that the tradition of the Rebo Kasan ceremony in Cigalontang Singaparna Tasikmalaya was carried out on the last Wednesday in the Safar Bula, on the same day residents were prohibited from traveling far away and work was postponed as much as possible on that day. Because there is a local belief that if a disaster occurs on that day, it will be difficult to treat it and it is difficult to find an antidote. Therefore, on that day all residents gather together to hold prayers to avoid catastrophic reinforcements, so that what is expected from this tradition can come true. In addition, this tradition is carried out with the aim that we are always grateful to Allah SWT who has given His gifts in the form of sustenance, safety as well as harmony, peace, and being able to strengthen the bonds of brotherhood among Muslims. So that researchers are very interested in researching more deeply about the Rebo Kasan tradition carried out by the Cigalontang Tasikmalaya community. The method used in this study is a qualitative method with an ethnographic approach. Qualitative research methods with an ethnographic approach describe and describe phenomena and realities in the field, such as about life which includes a person's attitude, or regarding the position of social movements, organizations, languages, symbols and so on. The results of this study indicate that the implementation of the Rebo Kasan tradition carried out by the Cigalontang Tasikmalaya community is a tradition that is usually carried out every year. The community expresses their diversity and follows these religious rituals in a solemn and solemn manner. The Rebo Kasan tradition in the Cigalontang Tasikmalaya community has values, social, culture and religion. As a social value, the people of Cigalontang can strengthen friendship with their neighbours. Then as a cultural value, this tradition is a cultural heritage from their ancestors which has been passed on to their generations from the past until now. Meanwhile, as a religious value, in the process of this tradition there are religious practices such as hajat prayers, reciting holy verses of the Koran, lectures, sadaqoh, praying and so on.